ABC of ear, nose and throat - Ludman, Harold; Bradley, Patrick J., 1949-; Ludman, Harold; Ludman, Harold (Malden, Mass. : Blackwell Pub. : BMJ Books, 2007)
This new edition of the best-selling ABC of Otolaryngology offers an up-to-date overview of otolaryngology, and head and neck surgery (ENT). Now in its fifth edition, the ABC of Ear, Nose and Throat advises on how best to manage patients with the most common ENT-related problems. Thoroughly revised and updated, this new edition includes extra chapters on facial pain, head and neck tumours, sleep apnoea and epistaxis, as well as recent advances in ENT evaluation and investigations (especially CT and MRI) and minimally invasive techniques. New material on voice, breathing and swallowing disorders
CONTENTS : Contributors; Preface to Fifth Edition; 1 Pain in the Ear; 2 Discharge from the Ear; 3 Hearing Impairment and Tinnitus in Adults; 4 Adult Hearing Rehabilitation and Cochlear Implants; 5 Childhood Hearing Loss; 6 Acoustic Neuromas and other Cerebello Pontine Angle Tumours; 7 Vertigo; 8 Facial Palsy; 9 Paranasal Sinus Diseases and Infections; 10 Facial Pain; 11 Sore Throats; 12 Breathing Disorders; 13 Swallowing Problems; 14 Snoring and Obstructive Sleep Apnoea; 15 Hoarseness and Voice Problems; 16 Trauma, Injuries and Foreign Bodies. 17 Epistaxis, Catarrh, Glossodynia, Halitosis and Somatization18 Neck Swellings; 19 Head and Neck Cancer; Index.
Rev. ed. of: ABC of otolaryngology / Harold Ludman. 1997.
Includes bibliographical references and index.
Keywords: Otolaryngology; Otorhinolaryngologic Diseases